A Patient With Encephalomyeloradiculoneuropathy Exhibiting a Relapsing–Remitting Clinical Course: Correlation of Serum and Cerebrospinal Fluid Anti-Neutral Glycosphingolipids Antibodies With Clinical Relapse - Nanaura, Hitoki; Kataoka, Hiroshi; Shima, Sayuri; Iwasa, Naoki; Eura, Nobuyuki; Sugie, Kazuma; Mutoh, Tatsuro; Ueno, Satoshi (Frontiers in Neurology, 2018)
Several patients who had a progressive clinical course involving both the central and peripheral nervous systems have been reported, but the diagnostic marker has been remained uncertain. More recently, such patients were reported to have namely “encephalomyeloradiculoneuropathy (EMRN)” associated with anti-neutral glycosphingolipid (GSL) antibodies. These antibodies were reported to disappear from the serum in the recovery phase, but whether this finding applies to the cerebrospinal fluid (CSF) remains uncertain. We describe a 67-year-old man with EMRN in whom we measured anti-neutral GSL antibodies in serial serum and CSF samples. During the disease course, the optical densities of the positive band against the background intensity ratio (– <0.3; ± ≥0.3 to <0.6; + ≥0.6 to <1.0; 2+ ≥1.0 to <2.0; 3+ ≥2.0) for serum and CSF anti-lactosylceramide (LacCer) antibodies were found to be as follows: 2+ and 1+ at the first admission, ± and – when the consciousness level improved after immunotherapy, – and 1+ at clinical relapse, and ± and – when the consciousness level improved after immunotherapy. This is the first time to document that clinical relapse occurred in EMRN, and at this time the negative anti-LacCer antibodies in CSF after the first course of immunotherapy turned positive, but this was not seen in serum samples.